SAT-LB128 A Case of Metformin Associated Lactic Acidosis and the Importance of Medication Reconciliation in End-Stage Renal Disease - Tsai, Karen (J Endocr Soc, 2020)
Background: Metformin is commonly used in the treatment of diabetes mellitus due to its low cost, ease of administration and titration, and favorable side effect profile as it does not cause weight gain and rarely causes overt hypoglycemia. An important yet rare side effect of metformin use is metformin associated lactic acidosis (MALA) which can be seen in patients with significant renal impairment and is associated with high mortality. Clinical Case: We present a 54-year-old man with hypertension, type 2 diabetes mellitus, and recently diagnosed end-stage renal disease (ESRD) on hemodialysis who presented with shortness of breath and syncope and found to have an elevated lactate to 40.5 mmol/L (reference range: 0.5-2 mmol/L). Notably, the patient was admitted at an outside hospital two and a half weeks prior for a new diagnosis of ESRD and initiated on hemodialysis three times a week. At the time of discharge from his prior hospitalization, he was instructed to continue his diabetes medications: metformin 1g twice a day, glipizide 10 mg twice a day, and pioglitazone 30 mg daily. The patient was admitted to the intensive care unit and found to have MALA. Nephrology was consulted and the patient clinically improved with hemodialysis. Within six hours of presentation, the patient’s clinical course rapidly improved with complete resolution of lactic acidosis and hemodynamic instability within 48 hours. Conclusion: Although metformin is the most commonly used drug in diabetes mellitus, the side effect of metformin associated lactic acidosis is rarely seen in the inpatient setting. Patients with ESRD are at high risk for complications resulting from poor medication management. However, because metformin is primarily renally cleared, it should be discontinued in those with significant renal impairment. With increased awareness and understanding of MALA, providers can prevent MALA by appropriately stopping or dose reducing metformin in patients with chronic kidney disease. Educating patients on their medications—including their uses, side effects, and drug-drug and drug-food interactions—could help reduce the aforementioned medication-related problems. Clinicians should have a high suspicion of metformin associated lactic acidosis in any patient presenting with multi-organ failure due to its variable clinical presentation. If MALA is suspected, providers should consult nephrology so that patients can be started on hemodialysis.